2015
DOI: 10.1155/2015/415082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Levetiracetam and Carbamazepine as Monotherapy in Partial Seizures

Abstract: Introduction. Levetiracetam (LEV) is a newer antiepileptic drug with better pharmacokinetic profile. Currently, it is frequently used for the treatment of partial seizures. The present study was undertaken to compare the efficacy and safety of LEV and Carbamazepine (CBZ) in partial epilepsy. Methods. This was a prospective, open labeled, randomized study. It was conducted in participants suffering from partial seizures after the approval of ethics committee and written informed consent. The first group receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
(31 reference statements)
3
19
0
Order By: Relevance
“…The rates of AEs in this study is similar to that reported by Suresh et al [25], and Fadare et al [10], who reported adverse effects rates of 36.6% and 37.6% respectively, although both studies used non-structured questionnaires. Other studies using adverse effect questionnaires have reported rates between 60-78% [6,26,27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The rates of AEs in this study is similar to that reported by Suresh et al [25], and Fadare et al [10], who reported adverse effects rates of 36.6% and 37.6% respectively, although both studies used non-structured questionnaires. Other studies using adverse effect questionnaires have reported rates between 60-78% [6,26,27].…”
Section: Discussionsupporting
confidence: 90%
“…The high rates of memory impairment are similar to reports by Suresh et al and Eddy et al [25,30]. Whereas a study carried out in the south-south region of Nigeria did not report significant memory impairment in patients on AEDs [31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result was supported by a study done by SS Hassan et al were the percentage change seen was 34.82%. 11 Subgroup analysis was also done in present study where different aspects of QOLIE-10 scores were compared which showed improvement in all spheres. The mean change in epilepsy effect (5.25±1.18), mental effects (5.39±1.20) and role function effects (7.44±1.42) ( Table 4).…”
Section: Discussionmentioning
confidence: 97%
“…15 An estimated 6-10 million people in India suffer from epilepsy which accounts for nearly 1/5 th of global epilepsy burden. 16 Higher number of ADEs is seen with Phenytoin, as it is one of the most frequently prescribed AED for seizure disorder because of its established efficacy since many years. Antiretroviral medications have also been associated with cutaneous ADE, ranging from mild exanthemas to lifethreatening reactions, such as SJS or TEN.…”
Section: Discussionmentioning
confidence: 99%